[Diana Straub 3]
1970 children playing in park, fishing, bathing, 1950 newborn baby&mother, girls playing, Skating Rink, walking in the forrest, grandpa, 1952 funny scenes of a company, car with mercedes symbol, Badacsony house of Kisfaludy, airshow, chopper, parachutung, family, birthday cake&2candle, children&spotty ball, playground&rabbit, 1960 May Day, amusment park, Balaton